DAMPAK PEMBERIAN ZPT DAN POC TERHADAP PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium ascalonicum L.) - Efrata Barus; Riduan Sembiring; Meriksa Sembiring (JURNAL AGROTEKNOSAINS, 2021)
This study aims to determine the ZPT and POC intractions that can affect the growth and production of onion plants. This reserch was carried out in Gurubenua Village, Munte District, Karo Regency, Nourth Sumatra, with a height of ±1175-1350 meters above sea level. This research was conducted from June 2019 to September 2019, using the Factorial Randomized Block Design (RBD) method consisting of two regulatory factors, the first dose of ZPT with symbol A consisting of 4 levels, namely: No dosing (A0), 0,75ml/ liter of water (A1), 1,5ml/ liter of water (A2), and 2,25ml/ liter of water (A3). Second is the POC dose with the symbol P consisting of 4 levels, namely: Without dosing (P0), 1,5ml/ liter of water (P1), 3ml/ liter of water (P2), and 4,5ml/ liter of water (P3). Approved, 16 preparations were obtained, with two replications. The data analyzed the F test variance at the 5% level. If there is a significant difference (p˂0.05), then try to continue with the DMRT test. The results of the studyprove the need for a real implementation of ZPT (p˂0.005) for height plant variables per sample, number of leaves per plotand number of tubers per plot, and not significant (p˃0.005) for variable measurements of tuber diameter per sample, plant weight per sample and plant weight per plot. The treatment of submitting POC must be real (p˂0.005) of the plant height variable per sample, number of leaves per sample, number of tubers per sample, and plant weight per sample and not significant (p˃0.005) to the variable influence of tuber diameter per sample and plant weight per plot.